Factors influencing the health satisfaction of users of public health and medical institutions in South Korea - Yoon, Kichan; Lee, Munjae (Frontiers in Public Health, 2023)
In this study, we investigated the health satisfaction levels of users of regional health and medical institutions in South Korea and the influencing factors. We included randomly selected 300 people with experience in using health and medical institutions from panel data targeting the entire nation. We used questionnaire (EQ-5D-5L) and sociodemographic characteristics to analyze the health satisfaction. EQ-5D-5L was used to measure health-related quality of life in five areas: mobility, self-management, daily activities, pain/discomfort, and anxiety/depression. Hierarchical linear regression analysis was performed in three steps to examine the factors influencing health satisfaction. The analysis showed that the health satisfaction was positively (+) correlated with monthly income, mobility, self-management, daily life, pain/discomfort, and anxiety/ depression, and negatively (-) correlated with the number of chronic diseases and type of health insurance. The influencing factors in Step 1 and 2 were chronic diseases (β = -0.380, -0.385), respectively. The influencing factors in Step 3 were pain/discomfort (β = 0.202), anxiety/depression (β = 0.257), and the number of chronic diseases (β = -0.222). The current data suggested that regional health and medical institutions should focus their services on residents with chronic diseases. Moreover, they should expand physical activities to relieve physical pain or discomfort and provide services related to mental health. To accomplish these, we suggested that the government will need to promote post-service health checkup results as a key project, provide user-customized services, provide online services utilizing ICT, expanding the government’s financial support, and building infrastructure.